As ferramentas da qualidade no auxílio ao processo de custeio de medicamentos - Favilla, Thiago Augusto Couto [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
With the highest demand on the market for quality and affordable products, some tasks of great importance for companies have become even more impacting, such as the pricing of products developed and the option of investing in the development of new products so that the company market in relation to its competitors. On the other hand, the globalization and internationalization of industries has further increased the complexity of production processes, making it difficult to make important decisions to manage a company operating in a competitive market. The objective of this study is to propose improvements to the cost prediction process and analysis of the financial viability of drugs under development in a large national pharmaceutical industry, in order to guarantee a greater efficiency in the cost forecasting, through the use of quality in the aid and identification of the factors that influence the cost of production of the medicines. This work can be classified as a case study, since it is characterized by a study about the use of quality tools on the process of costing products in development

Com a maior exigência do mercado por produtos de qualidade e de preços acessíveis, algumas tarefas de grande importância para as empresas se tornaram ainda mais impactantes, como a precificação dos produtos desenvolvidos e a opção de se investir no desenvolvimento de novos produtos para que a empresa possa ter grande representatividade no mercado frente aos seus concorrentes. Em contrapartida, a globalização e internacionalização de indústrias vêm aumentando ainda mais a complexidade dos processos produtivos, dificultando a tomada de decisões importantes para gerenciar uma empresa que atua em um mercado competitivo. O objetivo desse trabalho é propor melhorias para o processo de previsão de custos e análise da viabilidade financeira de medicamentos em desenvolvimento em uma indústria farmacêutica nacional de grande porte, de modo a garantir uma maior eficiência na previsão de custos, através da utilização de ferramentas da qualidade no auxílio e identificação dos fatores que influenciam o custo de produção dos medicamentos. Esse trabalho pode ser classificado como um estudo de caso, uma vez que se caracteriza por um estudo sobre o uso das ferramentas da qualidade sobre o processo de custeio de produtos em desenvolvimento
Quality tools to aid the drug costing process
Keywords: Gestão da qualidade total; Indústria farmacêutica; Controle de qualidade; Total quality management